The search for meaning Americans talk about what they believe and why - Berman, Phillip L. (New York Ballantine Books, 1990)
"What do Americans, as a people, believe in? What are the experiences that have transformed our lives? How does faith--in God, in human goodness, in politics, progress, money, or pleasure--illuminate our actions? These are the questions that Phillip L. Berman, editor of The Courage of Conviction, asked when he set off on a four-year, 35,000-mile odyssey to chronical America's moral imagination. The result of his quest is The Search for Meaning. This engrossing and radiantly insightful book is the first and only oral history of the relilgious and philosophical belilefs of contemporary Americans."--Publisher's description.
Book One -- Knockin' bark off trees -- Problems of evil -- War -- The color line -- Outcasts -- Survivors -- Book Two -- Hedonic calculus -- Young folks -- The nihilist, the hooker, and the chessman -- Earthly delights -- The muse -- In the public eye -- Home on the range -- Book Three -- True believers -- Investments of faith -- Visiting spirits -- Men of the cloth -- Alternative altars -- Motherhood.
Keywords: Interviews -- United States; United States -- Religion -- 1960-.